2009
DOI: 10.1111/j.1478-4408.2008.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐pass process for the continuous dyeing of polyester/unmercerised cotton blends with disperse/reactive dyes. Part 1: Investigation of limited colour depth of the dyed blend

Abstract: In the continuous dyeing of polyester/cellulose blends, the trend over the last 20 years, towards shorter production runs and greater numbers of fashion shades, has led to the development of more productive processes, in particular, the use of a one‐pass pad–dry–thermofix process for the application of disperse and reactive dyes. However, there are limitations to such a one‐pass process, of which the most important is the limited colour depth that can be achieved on polyester/unmercerised cotton blends. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…During the dyeing process, the disperse dye diffuses into the PES fibre and, although this occurs slowly, it results in high exhaustion values. As a general rule, dyes with small molecular structures tend to diffuse more quickly within the fibre; however, they are also more easily removed .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the dyeing process, the disperse dye diffuses into the PES fibre and, although this occurs slowly, it results in high exhaustion values. As a general rule, dyes with small molecular structures tend to diffuse more quickly within the fibre; however, they are also more easily removed .…”
Section: Resultsmentioning
confidence: 99%
“…Reactions with the dye molecule: (a) reaction of reactive dye and cellulose; (b) hydrolysis of reactive dye; and (c) mechanism proposed for the reaction of reactive dye and photolysed poly(N‐vinyl‐2‐pyrrolidone). *Stereochemistry not defined Source: Reactions (a) and (b) were adapted from Trotman …”
Section: Resultsmentioning
confidence: 99%
“…Polyester/cotton blended fabric is usually subjected to a two‐stage dyeing process in which the polyester component is dyed first, followed by dyeing of the cotton component . Several dye and process modifications have been investigated for successful shortening of the process . However, the two‐stage process still remains the norm for most of the dyeing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Although developments have been made both in the machinery [3] to handle the shorter runs (to make their processing more cost‐effective) and in the dyestuffs [5–7] used (to meet the fastness requirements), one of the major limitations of a one‐pass process is the limited colour depth that can be achieved on polyester/unmercerised cotton blends. The previous part of this study [1], which focused on the performance of the dyes (disperse/reactive) used in DyStar’s one‐pass (TTN) continuous dyeing process, showed that it was the reactive dyes which were responsible for the difficulty in achieving heavy shades, economically. It also suggested that the level of reactivity of the reactive dyes, most commonly recommended for use in this process, was not the prime reason for the poor performance.…”
Section: Introductionmentioning
confidence: 99%
“… One of the limitations of DyStar’s TTN one‐pass continuous dyeing process for dyeing polyester/unmercerised cotton blends with disperse and reactive dyes is its inability to achieve heavy depths economically and part 1 of this study indicated that the limitation could be attributed to the reactive dye [1]. In this study, the constituents of the pad liquor were varied to determine if the visual colour yield of selected reactive dyes could be improved.…”
mentioning
confidence: 99%